Retirement and the Poverty of the Elderly: The Case of Portugal - Albuquerque, Paula Cristina; Arcanjo, Manuela; Escária, Vítor Manuel; Nunes, Francisco José; Pereirinha, José António (Journal of Income Distribution®, 2011)
This article discusses whether transition to retirement may be associated with a greater probability of becoming poor. Having recourse to the European Community Household Panel (ECHP) for Portugal, the analysis is focused on a sample of individuals who retired in the period 1994-2001. Longitudinal analysis focuses upon income changes upon entering retirement. We relate the dynamics of household income changes for people who retire to personal and household characteristics. A multivariate probit model of the probability of low income at the time of retirement, conditional on not having a low income prior to retirement, is then put forward.